High temperature initiation and propagation of cracks in 12%Cr-steel turbine disks (Fracture and Structural Integrity, 2013)
This work aims to study the crack propagation in 12%Cr steel for turbine disks. Creep CrackGrowth (CCG) tests on CT specimens have been performed to define the proper fracture mechanics whichdescribes the initiation of the crack propagation and the crack growth behaviour for the material at hightemperature. Results have been used to study the occurrence of crack initiation on a turbine disk at the extremeworking temperature and stress level experienced during service, and validate the use of C* integral incorrelating creep growth rate on the disk component, in case C* is numerically calculated through FEM analysisor calculated by the use of reference stress concept.
Keywords: Creep Crack Growth